CLINICAL EFFECT OF TESTOSTERONE IN MEN WITH STABLE ANGINA - A. Ya. Kravchenko; V. M. Provotorov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study efficacy of testosterone undecanoate (TU) therapy in men with stable angina and androgen deficiency.Material and methods. The serum testosterone level was detected in 247 men (aged 51,6±1,8 y.o.) with stable effort angina. 60 patients with androgen deficiency additionally to basic angina therapy received TU (120-160 mg daily). 54 patients with androgen deficiency (control group) received only basic angina therapy. Dynamics of clinical and ECG manifestations of myocardial ischemia and quality of life (QOL) parameters was studied.Results. Androgen deficiency is revealed in 114 (46,2%) of patients. Therapy with TU during 3 months resulted in reduction of angina attacks and extent of myocardial ischemia (according to Holter ECG monitoring and stress test) as well as QOL improvement.Conclusion. Androgen deficiency is observed in 46,2% of men with stable angina. TU increases of antianginal therapy efficacy, improves QOL and is well tolerated.